Compressive strength of concrete with millet husk ash (MHA) as a partial replacement for cement - S.M. Auta; A.J. Shiwua; T.Y. Tsado (Инженерно-строительный журнал, 2015)
A study of compressive strength of concrete with millet husk ash (MHA) as partial replacement for ordinary Portland cement (OPC) is presented. The strength characteristics was investigated by casting and testing 54 specimen cubes sizing 100 mm x 100 mm x 100 mm for varied percentage replacements of cement (0 %, 10 % and 20 %) with water cement ratio of 0.65. These cubes were cured for 7 days, 14 days, 28 days and 35 days to target strength design of 25 N/mm2 at 35 days crushing. The result shows that at 35 days the compressive strength for 0 %, 10 % and 20 % replacements are 32.00 N/mm2, 25.56 N/mm2, and 23.18 N/mm2, respectively. It is clear that MHA as a pozzolanic material can be incorporated into cement in amounts of no more than 10 % replacement in order to develop a good and hardened concrete.